Topical corticosteroid therapy: clobetasol propionate 0.025% - Syed, Waseem Y.; Ranade, Minal A.; Agarwal, Anshu; Kumar, Pankaj; Mehta, Surjit S.; Deexith, Yeluri V. R. L. M.; Jain, Devendra; Saini, Nirmal K.; Patil, Sanjeev S.; Talavia, Parag A. (International Journal of Research in Medical Sciences, 2022)
Topical corticosteroids have been the cornerstone of treatment over the last six decades for various dermatoses characterized by dry, scaly, crusted, or erythematous skin as well as those associated with inflammation and pruritus. The potency of a topical steroid depends on the specific molecule, the amount of drug reaching the target, absorption through the skin (0.25%–3%), and the formulation. Clobetasol propionate (CP) 0.025% cream formulation is a potent, fifth-generation topical corticosteroid. It is approved by the United States Food and Drug Administration to be applied twice daily for the treatment of moderate-to–severe psoriasis in adults. This case series covers the clinical experience of various dermatologists, including their expert opinion on the safety and efficacy of ImpoyzTM (CP) cream 0.025% in different skin disorders.